Test of Self Por [decoded] trait no. 2 / Syafiq Abdul Samat - Abdul Samat, Syafiq (Faculty of Art and Design, 2021)
Inspired by some of the generative art made via programming, I was able to create my own algorithmic concept, using these “noises” as factors or variables to affect the creation of the proposed visual. In this case, difference in sound level may change the shape of a brush and introduce different colour at random time may affect the look of a render. However, since this is generative art, result often varies by each render, yet maintain recognizable similarities between the same algorithms. These process of collecting variables of available sounds and lights was the origin for the name “Hingarmera”, a wordplay of “Hingar” (means “noisy” in Malay language) and Camera. In this masterpiece, I present another variation of Hingarmera algorithm titled “Noise Per Dot", which mimics some of the traits of making a painting. Incoming real time feed (sound and light data) from the webcam will be divided into several columns and rows. For each section, the code will divide it again for several parts horizontally. Within each part, the code will sample a color, and will draw a rectangle based on sound volume level at the time the sample was taken; the louder, the taller the rectangle will be drawn. This process is repeated for the next part within the same section and continued for the next row beneath it per column. Intentionally, each drawn rectangle may overlap other rectangle, imitating overlapping brush strokes in a painting.